Comparative Evaluation of Apically Extruded Debris during Pulpectomy Procedure in Primary Molar Teeth Using Two Different Rotary Systems and Hand Files: An In Vitro Study - Komal Nanavati; Farhin Katge; Manohar Poojari; Shilpa Shetty; Aishwarya Kamble (International Journal of Dentistry)
Background. Successful outcome of endodontic treatment depends on chemomechanical preparation of the tooth. However, during canal preparation, debris may extrude through the apical foramen causing postoperative complications. The aim of this study is to evaluate and compare the amount of apically extruded debris during the pulpectomy procedure in primary molar teeth using two different rotary files and hand files. Materials and Methods. Distal roots of sixty extracted primary molars were divided into three groups: group A: Prime Pedo™ pediatric rotary files, group B: DXL-Pro Pedo™ pediatric rotary files, and group C: hand files. Myers and Montgomery experimental model was used. Preweighed Eppendorf tubes were used to collect apically extruded debris. The tubes were then placed in an incubator at 70°C for 5 days. The weight of the debris attained was determined. The data were analyzed using ANOVA and post hoc Bonferroni test. Results. Hand files produced more apical debris extrusion (P<0.05). Prime Pedo™ pediatric rotary files produced the least debris (P<0.05). Conclusion. Prime Pedo™ and DXL-Pro Pedo™ pediatric rotary files extruded significantly lower amount of debris apically during pulpectomy as compared to hand files. Rotary files can be considered an alternative to hand files in pediatric endodontics.